European discourse: what difference does it make in the national coordination of the European agenda?. Issue 4 (7th August 2020) - Švihálková, Johana; Kaniok, Petr
ABSTRACT: Coordination systems of the European agenda in EU Member states have been mostly examined thought three traditional neo-institutional approaches. Historical, rational choice and sociological institutional approaches greatly vary in explaining what causes changes in EU affairs coordination structures. We propose that such disagreement is caused by their focus on exogenous static changes, not paying sufficient attention to the role that daily communication of EU affairs may have on the way they are coordinated. Our article fills this gap by analysing the impact of communicative discourse of EU issues in the Czech Republic. Using discursive institutionalism as a point of departure and using critical discursive analysis, we found that the case of a coalition with pro-European discourse did not confirm the expectations about the decentralization of coordination system. On the contrary, the coordination system moved back towards a centralized system.